Transformation of Science Learning with Android Applications: Improving Learning Outcomes and Student Activity Through “Marbel Sains SD 4-5” - Ponco Nur Hidayah; Waris; Rina Sugiarti Dwi Gita (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluated how well the Android-based learning application “Marbel Sains SD 4-5” helps elementary school students learn science better. The study used a quasi-experimental design with a non-equivalent control group, involving 178 students selected from a pool of 3,650 students in 33 schools. Participants were divided into high-achieving and low-achieving groups, with each having a control group (conventional learning) and an intervention group (Marbel Sains), totaling 44 students in each group. The data collection tool consisted of a HOTS C4-level questionnaire designed to assess learning outcomes, along with an observation sheet rooted in the active learning model to evaluate student engagement. Due to the non-normal distribution of the data, the Friedman test for repeated measures and the Kruskal-Wallis test for group comparisons were used for analysis. The “Marbel Sains” application significantly improved learning activities and outcomes compared to the conventional method, highlighting its effectiveness as an interactive learning tool.